Weight gain during external fixation. (March 2013) - Culotta, Brad A.; Gilbert, Shawn R.; Sawyer, Jeffrey R.; Ruch, Alice; Sellers, Thomas
Abstract: Background/purpose: In our clinical practice we found that some patients treated with external fixation, especially those with Blount disease, had notable weight gain. We hypothesized that correction of Blount disease using external fixation would be associated with weight gain and that the weight gain would be greater than that seen in other patients. Methods: This was a retrospective chart review of patients with Blount disease at two children's hospitals. Patients with Blount disease were compared to patients treated with external fixation for fracture or other deformity. The data recorded included initial and post-treatment weight and time in external fixation. Within each group pre-operative weight was compared with post-treatment weight, and weight gain was compared between groups. Results: The study cohort comprised 39 patients with Blount disease and 13 control patients. The average age and weight of the patients with Blount disease and the controls were 12.8 years and 106.4 kg (1.7 × the 95th percentile weight for age) and 12.2 years and 52.4 kg (0.89 × the 95th percentile weight for age), respectively. Patients with Blount disease gained an average of 3.7 kg (range −12.5 to +43.1 kg) during 18 weeks of treatment (0.19 kg/week), and the controls gained an average of 4.1 kg (range −4.4 to +19 kg) over 17 weeks (0.247 kg/week). The weight gain during treatment was statistically significant for both groups, but was not statistically different between groups. Conclusion: Patients with Blount disease as well as those with other conditions treated with prolonged external fixation experience significant weight gain which could complicate rehabilitation or return to previous activity.